English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Hmm i'm kinda stuck on some homework proofs and wonder if anyone can help me?

Using the applications of Extreme Value Theorem, Intermediate Value Theorem, Mean Value Theorem, & Rolle's Theorem detemine the following questions.

1) Suppose f, g are continuous on [a,b], f(a) < g(a), f(b) > g(b). Prove f(x) = g(x) for some x E (a,b)

2) Suppose f is continuous on [0,1], 0 ≤ f(x) ≤ 1 for x E [0,1]. Prove f(x) = x for some x E [0,1]

3) a) For f as in problem 2, prove f(x) = -x for some x E [0,1]

b) If g is continuous on [0,1], g(0) = 0, g(1) = 1. Prove f(x) = g(x) for some x E [0,1]

2006-11-17 11:10:16 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

#1: Let h(x) = f(x) - g(x). Then h is a continuous function such that h(a) < 0 and h(b) > 0, so by the intermediate value theorem there exists a c in the interval (a, b) such that h(c)=0. But h(c) = 0 means f(c) = g(c), so there is a point in (a, b) where f(x) = g(x).

#3b (sic): f and g are continuous on (0, 1), f(0) ≥ g(0) = 0, f(1) ≤ g(1) = 1. If we have equality in either case then we are done. If not, then this meets the conditions of the functions in problem 1, so we may apply that result.

#2: Let g(x) = x. Apply the result of 3b.

#3a: This one must have a typo. f(x) is nonnegative over [0, 1], so the only way f(x) could equal -x is if f(0) = 0, and there's nothing guaranteeing that it does. Perhaps you mean f(x) = 1-x. In that case f(0) ≤ g(0) = 1, f(1) ≥ g(1) = 0, and so if h(x) = f(x) - g(x), h(0) ≤ 0, h(1) ≥ 0. If we have equality in either case then we are done. Else, we may invoke the intermediate value theorem much as we did in problem 1.

2006-11-17 11:48:33 · answer #1 · answered by Pascal 7 · 0 0

There are a couple of ways to do it I think you want d/dx(cos x) let d/dx(cos x) = t we know sin ^ 2 x + cos ^2 x = 1 differentiate both sides 2sinx d/dx(sinx) + (2 cos x ) t = 0 or 2 sinx cos x + 2t cos x =0 so t = - 2sinx cosx /(2cosx) = - sin x 2nd method let d/dx(cos x) = t we know exp(ix) = cos x + i sin x differentiate both sides i exp(ix) = t + i cos x devide both sides by i exp(ix) = -it + cos x = cos x -it equating imaginary part t = -sin x

2016-05-21 23:47:49 · answer #2 · answered by Anonymous · 0 0

fedest.com, questions and answers